Study Protocol for the Translating Research in Elder Care (TREC): Building Context through Case Studies in Long-Term Care Project (Project Two) - Dopson, S; Rycroft-Malone, J; Degner, L; Hutchinson, A; Morgan, D; Stewart, N; Estabrooks, C (BioMed Central, 2009)
Background: The organizational context in which healthcare is delivered is thought to play an important role in mediating the use of knowledge in practice. Additionally, a number of potentially modifiable contextual factors have been shown to make an organizational context more amenable to change. However, understanding of how these factors operate to influence organizational context and knowledge use remains limited. In particular, research to understand knowledge translation in the long-term care setting is scarce. Further research is therefore required to provide robust explanations of the characteristics of organizational context in relation to knowledge use. Aim: To develop a robust explanation of the way organizational context mediates the use of knowledge in practice in long-term care facilities. Design: This is longitudinal, in-depth qualitative case study research using exploratory and interpretive methods to explore the role of organizational context in influencing knowledge translation. The study will be conducted in two phases. In phase one, comprehensive case studies will be conducted in three facilities. Following data analysis and proposition development, phase two will continue with focused case studies to elaborate emerging themes and theory. Study sites will be purposively elected. In both phases, data will be collected using a variety of approaches, including non-participant observation, key informant interviews, family perspectives, focus groups, and documentary evidence (including, but not limited to, policies, notices, and photographs of physical resources). Data analysis will comprise an iterative process of identifying convergent evidence within each case study and then examining and comparing the evidence across multiple case studies to draw conclusions from the study as a whole. Additionally, findings that emerge through this project will be compared and considered alongside those that are emerging from project one. In this way, pattern matching based on explanation building will be used to frame the analysis and develop an explanation of organizational context and knowledge use over time. An improved understanding of the contextual factors that mediate knowledge use will inform future development and testing of interventions to enhance knowledge use, with the ultimate aim of improving the outcomes for residents in long-term care settings.